Strategic brand communication campaigns - Schultz, Don E.; Barnes, Beth E. (Lincolnwood, Ill. : NTC Business Books, 1999)
Marketing and communication in the twenty-first-century marketplace. Brands and branding. Building brand value. The IBC planning process and estimating customer value. Converting customer knowledge into IBC programs. Consumer behavior and information processing...
Keywords: Advertising; Advertising campaigns